Insights into audio-visual temporal perception in bipolar disorder and schizophrenia - Monica Gori; Maria Bianca Amadeo; Andrea Escelsior; Davide Esposito; Alberto Inuggi; Riccardo Guglielmo; Luis Polena; Juxhin Bode; Beatriz Pereira da Silva; Mario Amore; Gianluca Serafini (Current Research in Behavioral Sciences)
Our perception of the world and sense of self are deeply influenced by our perception of time. Research in psychiatric disorders has shown altered temporal perception across a variety of tasks, though the mechanisms behind these changes remain unclear. This study aims to explore temporal processing in patients with bipolar disorder (BD) and schizophrenia (SZ) by examining auditory, visual, and audio-visual temporal perception. The results revealed impaired temporal performance across all sensory modalities and the absence of auditory dominance in both patient groups. Specifically, in SZ patients, multisensory processing was associated with visual precision, while in BD patients, there was no such relationship with either visual or auditory precision. Notably, in SZ, visual precision was significantly linked to negative symptoms. Moreover, despite the lack of auditory dominance and similar deficits in unisensory performance, neither patient group benefited from redundant multisensory information in the temporal task. These findings highlight distinct patterns of temporal processing in BD and SZ compared to healthy controls, suggesting potential pathways for targeted interventions, such as integrating sensory training into clinical rehabilitative frameworks.